Enhancing Students’ Comprehension of Poetry Texts through the Integration of Project-Based Learning and Design Thinking - Fat-Hiyah Dwi Fitriani; Mujiono Mujiono; Gatot Sarmidi; Ritma Yuniasari (Universitas Cokroaminoto Palopo, 2026)
Poetry instruction in secondary schools sometimes limits students' full involvement in interpreting and appreciating literary works. The present research aimed to enhance students' understanding of poetic texts. In this regard, the study employed Project-Based Learning (PBL) and Design Thinking methodologies. The survey employed a Classroom Action Research study based on Kemmis and McTaggart's model, comprising three cycles of planning, action, observation, and reflection. The study involved 32 eleventh-grade students aged 16–18 from a public senior high school in Malang, Indonesia. Data were collected through observations, interviews, field notes, tests, and documentation. Reliability of the study was ensured through triangulation of constructs and procedures, and verification procedures were monitored throughout the research project. Results showed an increase in student engagement during lessons, from 68.75% to 93.75%. Obtaining mastery level increased the rate from 71.88% to 93.75%. Consequently, such trends resulted in a higher class average score, 84.13 to 85.86. Results from the qualitative analysis showed even stronger motivation, self-assurance, teamwork and desire to make sense of poetry. This makes it clear that, when it comes to students learning poetry, a conceptual step such as using PjBL together with Design Thinking will make learning poetry and greater interaction possible.